Factors influencing the investment decision behaviour among young Muslim adults in Malaysia - Mohd Nasir Samsulbahri; Norhamiza Ishak; Haneffa Muchlis Gazali; Pg Mohd Faezul Fikri Ag Omar; Nurul Izzati Abd Razak (Penerbit UMS, 2021)
The main objective of the study is to explore the factors influencing the investment decision behaviour among young Muslim adults in Malaysia, and in turn highlight gaps that exist in the academic literature on the variables. Particularly, the study employs the Theory of Planned Behaviour as the main framework with additional variables, namely financial literacy, herding behaviour, and perceived taqwa. This paper highlights the discussion on TPB factors and their relationship with investment decision behaviour among young Muslim adults. The outcome of this study shows that almost all variables are deemed to be associated with investment decision behaviour. This study provides a better understanding of young Muslim adults’ investment decision behaviour among academicians, regulators and practitioners. The paper extends the understanding of TPB to newly emerging contexts such as financial literacy, herding behaviour, and perceived taqwa in understanding factors influencing the investment decision behaviour among young Muslim adults.